An Insight into Distance Language Teaching/Learning from Secondary School Teachers’ and Learners’ Perspectives during and post COVID-19 in Saudi Arabia - Alshamrani, Dania; Alsuhaibani, Yasser (International Journal of Language and Literary Studies, 2023)
The aim of the study is to discuss the situation of implementing distance education from the perspective of secondary school English language teachers and learners in Saudi Arabia. The shift to distance education was determined on the 9th March and started on 15th March, 2020 respectively. The study has implemented a mixed-methods approach using two instruments; semi-instructed interviews and questionnaires; 1149 students and 398 teachers from both genders responded to the questionnaires, 3 teachers and 4 learners participated in the interviews. Results showed an overall acceptance for distance English language teaching and learning. The findings also revealed the main challenges for different aspects. From the management aspects, the findings confirmed an increase in teachers’ workload and learners’ assignments in distance learning that negatively affects the learning process. Turning to the educational issues, results indicated concerns about assessment accuracy and learner participation in distance learning. This study has found that technical issues generally play a vital role in missing classes and losing concentration.